Glucose measurement in cerebrospinal fluid compared to peripheral blood in dogs with central nervous system disease - Wolfe, Megan; Schlein, Lisa; Henry, Jamie; McGrath, Stephanie (Frontiers in Veterinary Science, 2025)
IntroductionGlucose in cerebrospinal fluid (CSF) is an easily measurable parameter that may correlate with inflammatory central nervous system (CNS) disease. The aim of this study was to evaluate CSF glucose concentration and CSF: peripheral blood glucose ratio (CBGR) in healthy dogs of various ages and dogs with inflammatory versus non-inflammatory CNS disease.MethodsThis was a single institution retrospective study. Dogs who had peripheral blood collection within 24 h of CSF tap were included. The CSF glucose measurement and CBGR were calculated for healthy dogs and for dogs with various categories of CNS disease.ResultsForty-one healthy dogs and 359 dogs with CNS disease were included. Mean (95% CI) CSF glucose in healthy dogs was 78.4 mg/dL (72.0–84.7) and mean CBGR was 0.80 (0.74–0.86). Among healthy dogs, there was a significant positive correlation between age and CBGR (ρ = 0.41) (p = 0.007). Non-Inflammatory Structural CNS disease had a significantly higher CSF glucose concentration than healthy dogs [87.8 mg/dL (84.2–91.4), p = 0.03]. There was no significant difference in mean CBGR compared to healthy dogs for Non-Inflammatory Structural CNS disease [0.81 (0.78–0.84), p = 0.98] or Idiopathic Epilepsy [0.75 (0.71–0.79), p = 0.28]. Mean CBGR for dogs with Inflammatory CNS disease [0.70 (0.65–0.74)] was significantly lower than that of healthy dogs (p = 0.02). When dogs were divided into more specific disease categories, there was no significant difference in CBGR compared to healthy dogs for Autoimmune [0.70 (0.66–0.75), p = 0.06], Infectious [0.67 (0.56–0.77), p = 0.15], or any other category.DiscussionHealthy dogs have a CBGR of approximately 0.80, but older age may affect this value. Altered CBGR may help distinguish inflammatory from non-inflammatory structural CNS disease.